MANAJEMEN MUTU PENDIDIKAN ISLAM DI ERA MASYARAKAT MODERN - Fauqiyah, Nuril; Subhan, Mohammad (Fakultas Agama Islam Universitas Islam Madura, 2025)
The quality of Islamic education is a strategic aspect that determines the success of the institution in producing a generation that excels intellectually, characterfully, and is based on spiritual values. This article aims to examine the concept, scope, improvement strategy, and practical study of the application of quality education in the era of modern society, with a focus on Islamic educational institutions. Using a literature study approach, this study explains that the quality of education includes the conformity of processes and results with the set standards, the needs of education service users, as well as Islamic values such as itqan (sincerity), ihsan (best quality), and amanah (responsibility). The scope of quality includes institutional, educator, student, learning processes, and integrated evaluation. The quality improvement strategy emphasizes the development of a quality culture, strengthening teacher competence, a sustainable evaluation system, and visionary leadership. A case study at the Tebuireng Islamic Boarding School shows that the synergy between Islamic boarding school traditions and modern innovations can produce a sustainable quality system, including academic learning, character development, and institutional management based on Islamic values. These findings confirm that the success of improving the quality of Islamic education is highly dependent on collective commitment, leadership integrity, and the application of adaptive management principles, so that Islamic educational institutions are able to compete globally without losing their Islamic identity.